THE EFFECT OF BARIATRIC SURGERY ON BREAST CANCER INCIDENCE AND CHARACTERISTICS: A COMPREHENSIVE SYSTEMATIC REVIEW - Suryadi, Rokhim; Supriyo, Bambang; Yulanda Putra, Yosie; Auliya, Ahsan; Hardiyansah, M. Yudhi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Obesity elevates estrogen levels and pro-inflammatory cytokines, increasing breast cancer risk via macrophage migration to breast tissue and stimulating epithelial proliferation. Observational studies suggest that intentional weight loss, such as through bariatric surgery, can mitigate this risk. This study aims to conduct a comprehensive systematic review, focusing on the impact of bariatric surgery on breast cancer incidence and characteristics using recent literature. Methods: The systematic review followed PRISMA 2020 standards and examined full-text English literature published between 2014 and 2024. This review excluded editorials, review papers from the same journal, and submissions without a DOI. Literature was sourced from online platforms such as PubMed, SagePub, and SpringerLink. Result: A total of  1,011 articles s were retrieved from online databases (PubMed, SagePub, and SpringerLink). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Bariatric surgery decreases overall cancer risk in women, especially for breast cancer, by lowering estrogen levels and altering tumor biology. It also improves glucose homeostasis and reduces insulin resistance, both linked to higher cancer risk.